Gestational Diabetes Mellitus - Mukesh Agarwal; Gurdeep S. Dhatt; Syed M. Shah (2010)
OBJECTIVE To determine the impact of the International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria on 1) gestational diabetes mellitus (GDM) diagnosis compared with the American Diabetes Association (ADA) criteria and 2) the fasting plasma glucose (FPG) to predict GDM. RESEARCH DESIGN AND METHODS In 10,283 pregnant women undergoing a 75-g oral glucose tolerance test (OGTT) for universal screening of GDM, two FPG thresholds (of the OGTT) were used to rule in and to rule out GDM. RESULTS The IADPSG and ADA criteria identified GDM in 3,875 (37.7%) women and 1,328 (12.9%) women, respectively (P < 0.0005). FPG thresholds of ≥5.1 mmol/l ruled in GDM in 2,975 (28.9%) women with 100% specificity, while <4.4 mmol/l ruled out GDM in 2,228 (21.7%) women with 95.4% sensitivity. FPG independently could have avoided the OGTT in 5,203 (50.6%) women. CONCLUSIONS The IADPSG criteria increased GDM prevalence nearly threefold. By circumventing a significant number of OGTTs, an initial FPG can greatly simplify the IADPSG diagnostic algorithm.